The Effect Of The New Normal Regulations Of The Covid-19 Pandemic On The Visist Of Patients Dental And Mouth - Tarianna Ginting; Putri Yunita Pane; Dameria Dameria; Efendi S Nainggolan; Suermawati Suermawati (International Journal of Health and Pharmaceutical (IJHP), 2022)
Covid-19 cases in Indonesia are increasing every day. This situation has an impact on people's lives, especially in the economic field due to social restrictions that occur in the community. Therefore, the government has started to gradually reopen social restrictions to save the economy. This initiative is known as "New Normal" where in this situation people's activities can run as usual but still follow health protocols to avoid transmission and spread of the virus. This study aims to determine the effect of the readiness of the new normal regulation of the Covid-19 pandemic, the effect of the readiness of PPE, human resources, work environment and health promotion on dental and oral patient visits. This type of research is an analytic survey with a cross-sectional design. The sampling technique in this study used inclusion and exclusion criteria where the population was sampled as many as 50 people and had met the inclusion criteria. The results of the bivariate test showed the effect of the New Normal Regulation (p=0.040), PPE (p=0.035), human resources (p=0.162), work environment (p=0.162), health promotion = 0.050. The results of this study concluded that there was an effect of the new normal regulation, PPE, and health promotion on dental and oral patient visits.